Is it possible that intellectual Capital Affects Performance? - Hasbiyadi Hasbiyadi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2021)
The impact of capital structure, good corporate governance, and intellectual capital on financial performance and firm value is examined in this study. The impact of financial performance on the value of a company. Examine the impact of capital structure, corporate governance, and intellectual capital on a company's financial performance. There were 193 financial reports in this study, with a sample size of 62 financial reports. Purposive sampling was used as a sampling technique. SEM-PLS is the analysis method used. The findings show that capital structure, good corporate governance, and intellectual capital have a positive and significant impact on financial performance and firm value. Firm value is influenced by financial performance in a positive and significant way. Good corporate governance and intellectual capital have a small but significant impact on firm value through financial performance. Through financial performance, capital structure has a negative and insignificant effect on firm value.